Research on the Trading Arrangement and Clearing Model of Medium- and Long-Term Inter-Provincial Markets Considering Security Constraints - Fu, Xueqian; Yang, Kaitao; Li, Guodong; Zeng, Dan (Frontiers in Energy Research, 2022)
In the process of deepening market-oriented reform, the most important thing in China is building a national unified electricity market system under a high renewable energy penetration scenario. The new round of market-oriented reform proposes to establish an inter-provincial electricity-trading arrangement. Due to imperfect market mechanisms and immature inter-provincial electricity markets, we investigate the electricity market operation system of the national unified electricity market. Existing transmission commitments, trading cycles, market participants, strategic bids, and clearing and settlement mechanisms are analyzed for inter-provincial medium- and long-term markets. For security reasons of interchange schedules, we propose a novel inter-provincial market-clearing model based on static security regions, which consider inter-provincial electricity transmissions and direct current power flows. The proposed market-clearing model is simulated and verified in a 3-bus system and an IEEE 30-bus system. The proposed clearing model and rational market theory are conducive not only to promoting renewable energy consumption but also to improving the linkages between inter-provincial medium- and long-term markets.